Inhibition of RORα/γ suppresses atherosclerosis via inhibition of both cholesterol absorption and inflammation - Cyrielle Billon; Sadichha Sitaula; Thomas P. Burris (Elsevier, 2016)
Objective: Cardiovascular diseases (CVDs) are the leading cause of mortality in Western countries. Atherosclerosis is a multi-step inflammatory disease characterized at early stages by accumulation of cholesterol in the arterial wall followed by recruitment of immune cells. We sought to determine if pharmacological suppression of RORα/γ activity is beneficial in treatment of atherosclerosis. Methods: To identify the role of RORα and RORγ in atherosclerosis, we used the LDL-R−/− mouse model of atherosclerosis placed on a high cholesterol diet treated with SR1001, a RORα/γ inverse agonist, for four weeks. Results: Our results demonstrate that treatment with the ROR inverse agonist substantially decreases plaque formation in vivo. The mechanism of the anti-atherogenic activity of the inhibition of RORα/γ activity appeared to be due to targeting two distinct pathways. SR1001 treatment reduced plasma low density lipoprotein (LDL) level without affecting high density lipoprotein (HDL) via increasing intestinal cholesterol excretion. Treatment with SR1001 also induced an anti-atherogenic immune profile that was characterized by a reduction in Th17 cells and an increase in Treg and Th2 cells. Our data suggest that RORα and RORγ play a critical role in atherosclerosis development by regulating at least two major pathways important in the pathology of this disease: cholesterol flux and inflammation. Conclusion: Our data suggest that pharmacological targeting of RORα/γ may be an effective method for treatment of atherosclerosis offering a distinct mechanism of action relative to statins. Keywords: Drug discovery, Nuclear receptor, Atherosclerosis, Cholesterol, Heart disease, ROR